Impact of a Coarse Material Sandwich Approach on the Performance of Geotextile-Reinforced Clay - Shooshpasha, Issa; Hasanzadeh, Ali; Salari, Vahidreza (International Journal of Integrated Engineering, 2025)
In many cases, the natural soil of the site does not have enough strength. Therefore, it is necessary to modify soil properties. In this regard, by adding one or more elements to the soil, its overall performance can be improved. The use of geotextile as an element in soil has attracted the attention of engineers, but investigating its performance in soil requires more study. Using a set of unconsolidated undrained (UU) triaxial tests, the behavior of geotextile-reinforced clay has been investigated in this research. Moreover, the impact of sandwiching nonwoven geotextile in a thin layer of sand (sandwich technique) on enhancing the shear strength of reinforced clay has been examined. Confining pressures (100, 200, 300, and 400 kPa), the number of geotextile layers (one, two, and three layers), and the thicknesses of the sand layers (zero, two, four, and six mm) are the variables considered for tests. The results revealed that the shear strength of clay rose as the number of geotextile layers increased. The efficiency of reinforcing clay with nonwoven geotextile can be related to a growth in the apparent cohesion of the reinforced sample. Considering the sandwich approach, it was found that with increasing the thickness of sand layers around the geotextile, the maximum deviatoric stress increased. For example, for the sample reinforced with two layers of geotextile under CP of 100 kPa, the increase rate of maximum deviatoric stress reached from 37 to 77% with increasing the thickness of the sand layer from 0 to 6 mm. Finally, the optimum thickness of the sand layer (4 mm) was identified, which led to the best enhancement in the performance of samples.